2023
DOI: 10.1002/aqc.3943
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of behaviour and spatial ecology of the small spotted catshark (Scyliorhinus canicula)

Abstract: 1. Shark populations have suffered dramatic declines across the world as a result of overfishing.2. Marine protected areas (MPAs) can help restore overfished populations; however, their effectiveness largely relies on understanding the ecology of the targeted species.3. This study investigated the spatial ecology of the intensely harvested but understudied small spotted catshark (Scyliorhinus canicula) through acoustic telemetry in the Cíes Islands, a small MPA in the north-west of the Iberian Peninsula.4. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…The telemetry data revealed the many instances (70) during when R. clavata individuals travelled outside the array to later return. These observations combined with the overall low residency index suggest that R. clavata true home range extends far beyond the limit of the study area and is in agreement with previous studies conducted on two different elasmobranchs species at this site (Leeb et al, 2021;Papadopoulo et al, 2023). A previous mark-recapture study found that most adult R. clavata were recaptured within 37 km of the release site (Chevolot et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The telemetry data revealed the many instances (70) during when R. clavata individuals travelled outside the array to later return. These observations combined with the overall low residency index suggest that R. clavata true home range extends far beyond the limit of the study area and is in agreement with previous studies conducted on two different elasmobranchs species at this site (Leeb et al, 2021;Papadopoulo et al, 2023). A previous mark-recapture study found that most adult R. clavata were recaptured within 37 km of the release site (Chevolot et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, R. clavata demonstrated high consistency in the sector taken to exit and re-enter the array with the majority of excursions heading to the Ría de Vigo. This result mirrors the excursion patterns of S. canicula at the same site (Papadopoulo et al, 2023) and suggests importance of the inshore waters of the Ría de Vigo for coastal elasmobranchs. Notably, although R. clavata appears to follow a specific route for entering and exiting the array, it is important to acknowledge that our approach points to the most probable direction taken after leaving the array, but it does not provide confirmation of the final destination of the excursions.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In the Mediterranean Sea, reports of ingestion and entanglement in sharks with various degrees of endangerment status have been reported [23,29,30]. Two shark species, the small-spotted catshark Scyliorhinus canicula and the blackmouth catshark Galeus melastomus, are not only commercially important species in the Balearic Islands in the western Mediterranean Sea, but the ecological assessment of these species, such as condition index, could be an indication of ecosystem health [31,32]. S. canicula is the most abundant elasmobranch species on the continental shelf [33].…”
Section: Introductionmentioning
confidence: 99%